Sociedad Civil versus Elites. Las transiciones a la democracia en España y Chile - Alvaro Soto (Les Cahiers de Framespa)
In both Spain and Chile, Civil Society and Elites participated in the process leading to the transition to democracy and in the transition itself, although their role and implication were different in each country. In Spain, Civil Society was the main actor until the foundational elections of June 15, 1977, after which elites play the major role. In Chile, this latter always played a predominant role, turning exceptionally to Civil Society, as for instance the campaign for registration on the electoral rolls prior to the October 5, 1988, plebiscite. After the plebiscite, its exclusive leadership encouraged social demobilization.